Does awake prone positioning prevent the use of mechanical respiratory support or death in COVID-19 patients on standard oxygen therapy hospitalised in general wards? A multicentre randomised controlled trial: the PROVID-19 protocol - Benjamin Planquette; Christophe Perrin; Thierry Boulain; Mai-Anh Nay; Louis Bernard; Laurent Plantier; Léa Colombain; Jérémy Clément; Aymeric Sève; Sylvie Druelle; Marine Morrier; Jean-Baptiste Lainé; et al. (BMJ Open)
Introduction COVID-19 is responsible of severe hypoxaemia and acute respiratory distress syndrome (ARDS). Prone positioning improves oxygenation and survival in sedated mechanically patients with ARDS not related to COVID-19. Awake prone positioning is a simple and safe technique which improves oxygenation in non-intubated COVID-19 patients. We hypothesised that early prone positioning in COVID-19 patients breathing spontaneously in medical wards could decrease the rates of intubation or need for noninvasive ventilation or death.Methods and analysis PROVID-19 is an investigator-initiated, prospective, multicentre randomised, controlled, superiority trial comparing awake prone positioning to standard of care in hypoxaemic COVID-19 patients in 20 medical wards in France and Monaco. Patients are randomised to receive either awake prone position plus usual care or usual care alone with stratification on centres, body mass index and severity of hypoxaemia.The study objective is to compare the rate of treatment failure defined as a composite endpoint comprising the need for non-invasive ventilation (at two pressure levels) or for intubation or death, between the intervention group (awake prone position plus usual care) and the usual care (usual care alone) group at 28 days.Ethics and dissemination The protocol and amendments have been approved by the ethics committees (Comité de protection des personnes Ouest VI, France, no 1279 HPS2 and Comité Consultatif d’Ethique en matière de Recherche Biomédicale, Monaco, no 2020.8894 AP/jv), and patients are included after written informed consent. The results will be submitted for publication in peer-reviewed journals.Trial registration number NCT04363463.